2022
DOI: 10.3389/fsurg.2022.801767
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Advanced Lung Cancer Inflammation Index as a Prognostic Indicator for Patients With Cholangiocarcinoma

Abstract: BackgroundThis study aimed to assess the clinical utility of the advanced lung cancer inflammation index (ALI) as a prognostic indicator for patients with cholangiocarcinoma (CCA) and construct a prognostic nomogram based on ALI.MethodsA total of 97 CCA patients who received radical resection were included. The optimal cut-off point for ALI was identified by X-tile analysis. COX regression analysis were used to identify risk factors of overall survival (OS) and disease-free survival (DFS). A predictive nomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Zhang X showed that preoperative ALI was an independent prognostic factor for GC patients undergoing curative gastrectomy [29]. ALI was also revealed to be a prognostic predictor for EC, liver cancer, and cholangiocarcinoma [30][31][32][33]. However, Pian G, Yin CZ, and Barth DA reported that there was no significant difference between ALI and DFS after gastrointestinal surgery [22,28,34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang X showed that preoperative ALI was an independent prognostic factor for GC patients undergoing curative gastrectomy [29]. ALI was also revealed to be a prognostic predictor for EC, liver cancer, and cholangiocarcinoma [30][31][32][33]. However, Pian G, Yin CZ, and Barth DA reported that there was no significant difference between ALI and DFS after gastrointestinal surgery [22,28,34].…”
Section: Discussionmentioning
confidence: 99%
“…Pian G, Yin CZ, and Barth DA et al demonstrated that there was no significant difference in ALI between patients receiving CRC surgery or GC surgery [ 22 , 28 , 34 ]. Others thought that a low ALI level would lead to a poor prognosis for gastrointestinal cancer patients [ 21 , 23 27 , 29 33 ]. Therefore, we aimed to explore the exact prognostic ability of ALI for patients with gastrointestinal cancer undergoing surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Wu et al . revealed that ALI outperformed NLR, PLR, monocyte-lymphocyte ratio (MLR), SII, and PNI in predicting OS and DFS in patients with cholangiocarcinoma by using time-dependent ROC analysis [ 16 ]. Thus, the ALI may have a higher discriminating value compared to other biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have consistently demonstrated the crucial role of inflammatory responses in the development of tumours. In recent years, several indicators reflecting the inflammatory status of the body, such as NLR, PLR, SII, and PNI, have shown correlations with the prognosis of various malignancies [7][8][9][10][11][12][13][14][15][16]. Notably, NLR, PLR, SII, and PNI have exhibited promising results in predicting the prognosis of non-small cell lung cancer and other malignancies.…”
Section: Introductionmentioning
confidence: 99%